Bio-mulching for conservation of in-situ soil moisture under mid hills of Meghalaya - EMILIA; RAY, LALA I.P.; MISHRA, G.P.; DAS, J. (Journal of Soil and Water Conservation, 2025)
Irrespective of highest annual average rainfall of North Eastern Region (NER), it makes almost difficult to grow second crop during the winter (rabi) season due to lack of suitable in situ soil moisture conservation measures, inadequate rainwater harvesting during rainy season or others. Incorporating bio/organic mulches can help in conserving in-situ soil moisture to a great extent. A field trial was taken up during 2022-23 to study the relative efficacy of these bio mulches in conserving the in-situ soil moisture with cultivars of garden pea as test crop. The experiment was laid out in a split plot design with four treatments (mulches), viz., i) no-mulch, ii) paddy straw mulch, iii) maize stover mulch and iv) weed mulch, applied @ 5 t ha-1 under main plot and four treatments (cultivars), viz., i) Arkel, ii) Punjab 89, iii) Pusa Pragati and iv) Pusa Prabal under sub-plot and replicated thrice. The soil moisture content in the root zone of mulched plot increased over no-mulch to a tune of 22.07, 12.00 and 4.64% for paddy straw mulch, weed mulch and maize stover mulch, respectively. Similarly, the highest green pod yield (8.51 t ha-1) was also recorded for paddy straw mulch and Punjab 89 variety recorded highest yield and water productivity (30.23 kg ha-1 mm-1). Paddy straw mulch can suitably utilised in the rice fallow areas of Meghalaya during winter season, which not only increases the yield, but also enhance the cropping intensity.